Correlation between peripheral arterial disease and stage of chronic kidney disease. - Phuangpaka Ungprasert (2018)
Atherosclerotic disease is the most common disease in clinical practice. Risk factors for the disease include diabetes, hypertension, dyslipidemia, smoking and chronic kidney disease (CKD). However, few studies have reported the correlation between peripheral arterial disease (PAD) and stages of CKD. Ankle brachial index (ABI) is a non-invasive method for detecting PAD with high sensitivity and specificity. We studied the prevalence of asymptomatic PAD in patients with each stage of CKD using ABI measurement. We conducted a study of patients with CKD classified by the Kidney Disease Outcomes Quality Initiative classification (K/DOQI classification) who attended at outpatient clinics. The patients with symptomatic PAD will be excluded. The participants will be sent to ABI measurement for the diagnosis of PAD, defined as ABI less than 0.9 The total number of patients who had been enrolled in the study was 201; Male 55%. Mean age was 65.16 +/- 11.3 years. 22.4% of the patients have ABI less than 0.9 which was associated with older age, being female, and having lower diastolic blood pressure (p = 0.002, < 0.001, < 0.0001, respectively) . Diabetes and coronary artery disease were higher in patients with abnormal ABI but with no statistical significance. No difference in other risk factors, for example, hypertension, dyslipidemia and smoking, was detected. Abnormal ABI was frequently seen in the patients with more advanced CKD and mean ABI was lower in patients with more advanced CKD stage. The meanABI of stage 4 and 5 CKD patients was lower than that of stage 1 and 2 (p < 0.05). The prevalence of asymptomatic PAD increased with more advanced stage of CKD.